1998
DOI: 10.1016/s0735-1097(98)00396-9
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with pediatric cardiac catheterization

Abstract: Complications continue to be associated with pediatric cardiac catheterization. Efforts should be directed to improving equipment for flexibility and size, and finding alternative methods for vascular access. Patient age and interventional studies are risk factors for morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
284
8
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(318 citation statements)
references
References 27 publications
18
284
8
8
Order By: Relevance
“…Definitions and surveillance methods for diagnosis of the problem are highly variable. Still, it is generally accepted that venous or arterial thrombosis is one of the most frequent adverse events after cardiac catheterization in children [595][596][597] and that this risk can be reduced by procedural anticoagulation. 160,598,599…”
Section: Thromboprophylaxis During Diagnostic and Interventional Cardmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitions and surveillance methods for diagnosis of the problem are highly variable. Still, it is generally accepted that venous or arterial thrombosis is one of the most frequent adverse events after cardiac catheterization in children [595][596][597] and that this risk can be reduced by procedural anticoagulation. 160,598,599…”
Section: Thromboprophylaxis During Diagnostic and Interventional Cardmentioning
confidence: 99%
“…Recent studies indicate a much lower incidence of vascular compromise from cardiac catheterization, reaching <5%. 595,603,604 However, almost no report includes risk stratification (age, size, procedural duration, size of catheter/ introducer, efficiency and monitoring of thromboprophylaxis during the procedure, patient predisposing factors). In addition, there is no standard surveillance methodology used regularly after the procedure to seek clinically silent events.…”
Section: Incidence and Significance Of The Problemmentioning
confidence: 99%
“…Incidence of major complications in diagnostic or therapeutic cardiac catheterisations ranges from 0.14% to 11% according to various studies [14][15][16] . This indicates that our safety standards are comparable to most of the published data and by performing the procedures with minimal resources we have not compromised on patient safety.…”
Section: Have We Lowered the Pole? Comparable Data From Other Studiesmentioning
confidence: 99%
“…In addition, an incidence of major complications (defined as potentially life-threatening events) less than 3% is also attainable. 13,14 Another study showed that fewer than 4% of transcatheter interventional procedures should require surgical intervention because of complications. 15 Furthermore, in radiofrequency ablation procedures, data show that permanent complete heart block rates less than 2% are common.…”
Section: Cardiac Catheterizationmentioning
confidence: 99%